LASER INDUCED THERMOMECHANICAL EFFECT IN HYBRID ORIENTED LIQUID CRYSTAL - Hakobyan, M.R. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2015)
In the paper laser induced thermomechanical flow and oscillations in hybrid oriented nematic liquid crystals (NLC) are theoretically predicted. The effect is conditioned by the hydrodynamic flow tendency to reduce the curvature of the “flexible ribbon” of hybrid NLC.
Keywords: nematic liquid crystals, thermomechanics, heat flux